ADOPSI MOBILE PAYMENT DI ERA TRANSFORMASI DIGITAL : PADA GENERASI Z - Juinta Ardiyanti; Dewita Puspawati (JURNAL ILMIAH EDUNOMIKA, 2025)
This study aims to analyze the impact of mobile skillfulness and personal innovation on behavioral intention through perceived usefulness in the use of mobile payment services, and the impact of perceived risk in the use of mobile payment services, with a particular focus on Generation Z (ages 12-27). Data were collected through a questionnaire adapted from the Technology Acceptance Model (TAM), involving 181 Generation Z respondents in Indonesia. The sampling method used was non-probability sampling with snowball sampling technique. Data analysis was conducted using Structural Equation Modeling-Partial Least Squares (SEM PLS). The results showed that mobile skillfulness did not have a significant effect on behavioral intention. However, personal innovation, perceived usefulness and perceived risk had a significant effect on behavioral intention. Mobile skillfulness and personal innovation had a significant effect on perceived usefulness. On the other hand, mobile skillfulness and personal innovation significantly influenced behavioral intention through perceived usefulness.